Subpopulation treatment effect pattern plot analysis: a prognostic model for distant recurrence-free survival to estimate delayed adjuvant chemotherapy initiation effect in triple-negative breast cancer - Ferreyra Chombo, Yomali Aroa (2024)
Artículo sustentado el 5 de junio 2024 para la obtención del título profesional de Bioingeniera.